MELACAK AKAR PENDIDIKAN ISLAM DALAM SISTEM PENDIDIKAN NASIONAL INDONESIA - S. Pettalongi, Sagaf (Paedagogia: Jurnal Pendidikan, 2017)
The roots of Islamic education in Indonesia can be traced from the existence and role of Islamic education which have been acted before Indonesia's independence. Islamic education so that was born and developed until now, it has become an integral part of the national education system, because in the value of education and institutional Islam was born and developed before the establishment of the national education system. It appears from the role of madrasah or Islamic boarding schools in various regions in Indonesia. After independence and the national education system is established, Islamic education was later recognized as part of the sub-national education system. The enactment of Law No. 20 of 2003 on the national education system emphasized the existence of Islamic education as part of the national education Islamic education is not only a sub-national education system but has become part of the national education system.